Health Profiles of Clients in Substance Abuse Treatment: A Comparison of Clients Dependent on Alcohol or Cocaine With Those Concurrently Dependent. (6th December 2014) - Macdonald, Scott; Pakula, Basia; Martin, Gina; Wells, Samantha; Borges, Guilherme; Roth, Eric; Salmon, Amy; Stockwell, Tim; Callaghan, Russell C.
<x xml:space="preserve">Abstract</x> The purpose of this study was to assess whether, among clients receiving substance abuse treatment (n = 616), those dependent on alcohol or cocaine differed significantly from those concurrently dependent on both drugs in terms of physical, mental, social, and economic harms as well as substance use behaviors. Methods: Clients from five substance abuse treatment agencies presenting with a primary problem of cocaine or alcohol were classified into three groups as dependent on: (1) alcohol alone, (2) cocaine alone, or (3) both cocaine and alcohol (i.e. concurrent dependence). Participants completed a self-administered questionnaire that included details of their drug and alcohol use, physical health, mental health, social health, economic health, and demographic characteristics. Results: The concurrent group drank similar amounts of alcohol as those in the alcohol group and used similar amounts of cocaine as the cocaine group. The alcohol group had significantly (p < .05) poorer health profiles than the concurrent group across most variables of the four health domains. An exception was significantly more accidental injuries (p < .05) in the alcohol group. In both bivariate and multivariate analyses, the concurrent group had significantly (p < .05) more accidental injuries, violence, and overdoses than the cocaine group. As well, the concurrent group had significantly (p < .05) higher scores on the anxiety and sexual compulsion scales than the cocaine group, controlling for demographic variables. Conclusion: These findings can aid health care professionals to better respond to issues related to concurrent dependence of cocaine and alcohol.